2018
DOI: 10.1016/j.chemosphere.2017.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive impacts of dietary methylmercury in yellow perch (Perca flavescens) and zebrafish (Danio rerio)

Abstract: The purpose of this study was to evaluate the effects of environmentally relevant dietary MeHg exposures on adult female yellow perch (Perca flavescens) and female zebrafish (Danio rerio) ovarian development and reproduction. Yellow perch were used in the study for their socioeconomic and ecological importance within the Great Lakes basin, and the use of zebrafish allowed for a detailed analysis of the molecular effects of MeHg following a whole life-cycle exposure. Chronic whole life dietary exposure of F zeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
2
3
0
Order By: Relevance
“… , However, it is important to reiterate that these concentrations are representative of fish muscle concentrations found in freshwater ecosystems in North America. ,,, The amount of dietary Hg female FHM transfer to eggs is small and resulted in WW Hg concentrations in exposed larvae that were roughly 0.04 ÎŒg/g higher than those of controls ( n = 7 clutches/treatment, Table S1). ,, Nevertheless, the results reported herein add to the body of evidence indicating this rate of transfer is sufficient to induce developmental toxicity in several species of teleosts. ,,− …”
Section: Resultssupporting
confidence: 91%
“… , However, it is important to reiterate that these concentrations are representative of fish muscle concentrations found in freshwater ecosystems in North America. ,,, The amount of dietary Hg female FHM transfer to eggs is small and resulted in WW Hg concentrations in exposed larvae that were roughly 0.04 ÎŒg/g higher than those of controls ( n = 7 clutches/treatment, Table S1). ,, Nevertheless, the results reported herein add to the body of evidence indicating this rate of transfer is sufficient to induce developmental toxicity in several species of teleosts. ,,− …”
Section: Resultssupporting
confidence: 91%
“…Overall, the enriched pathways were related to various functions including stress response (adenosine monophosphateactivated protein kinase signaling pathway, FoxO signaling pathway), synthesis and metabolism of biomolecules (glutathione, carbohydrates, steroids), promotion of cell growth, proliferation, and metabolism (PI3K-Akt signaling pathway), DNA repair, mineral absorption, immune response (cytokine-cytokine receptor interaction and antigen processing and presentation), muscle contraction (regulation of actin cytoskeleton), fatty acid and energy metabolism (fatty acid elongation, carbon metabolism), and cell death (apoptosis, ferroptosis, necroptosis). These pathways have similarly been identified in previous transcriptomic studies concerning methylmercury exposure in fish species including rainbow trout (Liu et al, 2013), zebrafish (DeBofsky et al, 2018;Hausen et al, 2018;Zhu et al, 2019), Atlantic cod (Yadetie et al, 2013), and European cusk (Olsvik et al, 2021). Furthermore, an overall examination of the Comparative Toxicogenomic Database (CTD; North Carolina State University, 2022) showed that many of these same pathways were dysregulated in response to exposure to methylmercury compounds (i.e., the top three were metabolism, immune system, and signal transduction).The significantly enriched pathways with the lowest BMD values (i.e., those with pathway BMD values below 10 ppb) included those involved in mineral absorption, metabolism, and biosynthesis (e.g., glutathione metabolism and steroid biosynthesis), and ferroptosis.…”
Section: Pathway-level Transcriptomic Bmd Enrichment Analysissupporting
confidence: 57%
“…Stained slides were digitally scanned for analyses using Nano Zoomer digital pathology system (Hamamatsu Photonics K.K.). To determine the number of clearly visible hepatocytes, hepatocyte diameter and number of Kupffer cells, a 10,000 mm 2 area of similar location on each serial section was identified (Debofsky et al, ; Kovi et al, ). Digital measurements of hepatocyte diameters were accomplished using NDPview2 desktop software package (v. 2.6.13, Hamamatsu Photonics).…”
Section: Methodsmentioning
confidence: 99%
“…The following parameters were determined on 100 ÎŒl serum for each sample: albumin, alkaline phosphatase, alanine aminotransferase, amylase, calcium, globulin, glucose, total bilirubin, inorganic phosphorus and total protein. identified (Debofsky et al, 2018;Kovi et al, 2011). Digital measurements of hepatocyte diameters were accomplished using NDPview2 desktop software package (v. 2.6.13, Hamamatsu Photonics).…”
Section: Sample Processing and Analysismentioning
confidence: 99%